Zuogui Wan ameliorates high glucose-induced podocyte apoptosis and improves diabetic nephropathy in db/db mice - Zhu, Bingbing; Fang, Ji; Ju, Zhengcai; Chen, Ying; Wang, Li; Wang, Hao; Xing, Lina; Cao, Aili (Frontiers in Pharmacology, 2022)
Zuogui Wan (ZGW), a well-known traditional Chinese medicine (TCM), has been used to nourish “Kidney-Yin” for a long time in China, implying a protective effect on the kidney. The aim of the present study is to investigate the effect of ZGW on high glucose-induced podocyte apoptosis and diabetic nephropathy (DN) in db/db mice. ZGW (1 g/kg−1/day−1) was administered intragastrically to db/db mice for 8 weeks. HPLC was used for identifying the components of ZGW, biochemical and histopathological approaches were used for evaluating its therapeutic effects, and cultured mouse podocytes were used for further exploring its underlying mechanism in vitro. ZGW improved renal function and podocyte loss and also normalized kidney reactive oxygen species production in db/db mice. The cytotoxicity of ZGW on mouse podocytes was assessed by the LDH assay. The effect of ZGW on podocyte viability and apoptosis was determined with CCK-8 and Annexin-V/PI staining by treatment with high glucose. ZGW attenuated podocyte apoptosis, and oxidative stress was detected by the peroxide-sensitive fluorescent probe 2′,7′-dichlorodihydrofluorescein diacetate (DCF-DA) staining in a dose-dependent manner. Furthermore, ZGW decreased the expression of caspase-3 and phospho-p38 in both the kidney cortex and high glucose-treated podocytes. Thus, our data from in vivo and in vitro studies demonstrated that ZGW improved renal injury in diabetes by inhibiting oxidative stress and podocyte apoptosis.